THE EFFECTS OF PALMVITEE ON HUMAN NASAL SEPTAL CHONDROCYTES CULTURE EXPANSION AND CARTILAGE RECONSTRUCTION - B.H.I. Ruszymah; B.S. Aminuddin; A. Gapor; H. Fuzina (ASEAN Journal on Science and Technology for Development, 2005)
Palmvitee may act as a beneficial supplement to cartilage tissue engineering which is currently still has certain limitation on chondrocyte expansion and dedifferentiation. Our objectives in thisstudy were to evaluate the effects of Palmvitee on the growth kinetic and phenotype gene expression of human nasal septal chondrocytesin monolayer expansion as well as cartilage reconstruction via tissue engineering technology. Human chondrocytes were cultured inmediums containing various Palmvitee concentrations. Among the different test groups, the medium containing Palmvitee at 3 ?g/ml supported the highest chondrocyte growth rate. The gene expression in monolayer chondrocytes culture supplemented with 3 ?g/ml Palmviteedemonstrated similar results as in control. Cultured chondrocytes from the medium added with 3 ?g/ml Palmvitee were then mixed with Pluronic F127 for cartilage reconstruction in nude mice model. Palmvitee supplementation supported the engineered cartilage development as shown in the histological and gene expression analysis on engineered tissue after 8 weeks of implantation. Therefore, Palmvitee at 3 ?g/ml is beneficial for the human nasal septal chondrocytes monolayer expansion and cartilage engineering.